Kikujiro [videorecording (DVD)] - Yoshiyuki, Kazuko, 1935-; Bito Takeshi; Sekiguchi, Yusuke (Columbia TriStar Home Video, 2000)
Lonely nine-year-old Masao leaves Tokyo in search of his mother, whom he has never met. He's accompanied on his journey across the Japanese countryside by the surly, middle-aged crook Kikujiro, who is none too happy being the chaperone. When Kikujiro gambles away all the travel money, the two must rely on their wits and the kindness of strangers.